2019
DOI: 10.1371/journal.ppat.1007680
|View full text |Cite
|
Sign up to set email alerts
|

USP49 negatively regulates cellular antiviral responses via deconjugating K63-linked ubiquitination of MITA

Abstract: Mediator of IRF3 activation (MITA, also known as STING and ERIS) is an essential adaptor protein for cytoplasmic DNA-triggered signaling and involved in innate immune responses, autoimmunity and tumorigenesis. The activity of MITA is critically regulated by ubiquitination and deubiquitination. Here, we report that USP49 interacts with and deubiquitinates MITA after HSV-1 infection, thereby turning down cellular antiviral responses. Knockdown or knockout of USP49 potentiated HSV-1-, cytoplasmic DNA- or cGAMP-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 67 publications
2
34
0
Order By: Relevance
“…Eight-week-old male and female KP, KP7 or KL mice were intranasally injected with Ad-Cre followed by various Quantitative real-time PCR. These experiments were performed as previously described 54,55 . Total RNA was extracted from tumor or normal tissues or cells using TRIzol reagent (Invitrogen), and the first-strand cDNA was reversedtranscribed with All-in-One cDNA Synthesis SuperMix (Biotool).…”
Section: Discussionmentioning
confidence: 99%
“…Eight-week-old male and female KP, KP7 or KL mice were intranasally injected with Ad-Cre followed by various Quantitative real-time PCR. These experiments were performed as previously described 54,55 . Total RNA was extracted from tumor or normal tissues or cells using TRIzol reagent (Invitrogen), and the first-strand cDNA was reversedtranscribed with All-in-One cDNA Synthesis SuperMix (Biotool).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that USP49 interacts with p53, dual-specificity protein phosphatases (DUSP), or FKBP51 in the nucleus, and consequently suppresses the ubiquitination of these proteins (Luo et al, 2017; Tu et al, 2018; Zhang et al, 2019). Regarding innate immunity, it can negatively regulate cellular antiviral responses via the deconjugation of K63-linked ubiquitin in STING, an adaptor protein that senses cytoplasmic DNA and is involved in various innate immune responses (Ye et al, 2019). Our data indicate that although USP49 is mainly distributed in the nucleus, it also exists in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The plasmid encoding GST-Ub-Tandem Ubiquitin Binding Entity (TUBE) was previously described and kindly provided by Dr. M. Gyrd-Hansen (University of Oxford, Oxford, UK; Fiil et al, 2013 ). GST-TUBE was expressed in Escherichia coli (DE3) and purified with a GST column as previously described ( Ye et al, 2019 ; Zhao et al, 2018 ). To analyze ubiquitinated KPNA2 or IRF3, GST-TUBE was incubated with cell lysates and pulled down by GST beads.…”
Section: Methodsmentioning
confidence: 99%